2016
DOI: 10.1111/ajt.13515
|View full text |Cite
|
Sign up to set email alerts
|

Practices for Supporting and Confirming Decision-Making Involved in Kidney and Liver Donation by Related Living Donors in Japan: A Nationwide Survey

Abstract: This nationwide survey investigated the actual practices for supporting and confirming the decision-making involved in related living-organ donations in Japan, focusing on organ type and program size differences. Answers to a questionnaire survey were collected from 89 of the 126 (71%) kidney and 30 of the 35 (86%) liver transplantation programs in Japan that were involved in living-donor transplantations in 2013. In 70% of the kidney and 90% of the liver transplantation programs, all donors underwent ''third-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A survey of 30 out of 35 LDLT programs in Japan indicated that 83% of the responding programs include the psychiatrist performing the donor evaluation in standard postdonation follow-up and that 93% of LLDs are offered the care of the mental health specialist. [33] Most programs did not provide psychosocial follow-up for declined donors perhaps in the context of Mathur's findings that nondonors' quality of life was better than the living donors'. [34] Understanding the impact of donor decline will be critical as US LDLT programs re-evaluate risk assessment across all aspects of the donor evaluation (medical, anatomical, and psychosocial) in an attempt to safely expand LDLT, with the aim of offering transplant opportunity to more patients with end-stage liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of 30 out of 35 LDLT programs in Japan indicated that 83% of the responding programs include the psychiatrist performing the donor evaluation in standard postdonation follow-up and that 93% of LLDs are offered the care of the mental health specialist. [33] Most programs did not provide psychosocial follow-up for declined donors perhaps in the context of Mathur's findings that nondonors' quality of life was better than the living donors'. [34] Understanding the impact of donor decline will be critical as US LDLT programs re-evaluate risk assessment across all aspects of the donor evaluation (medical, anatomical, and psychosocial) in an attempt to safely expand LDLT, with the aim of offering transplant opportunity to more patients with end-stage liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to a perceived lack of need for mental health check-ins, lack of program resources, or reliance on community mental health services. A survey of 30 out of 35 LDLT programs in Japan indicated that 83% of the responding programs include the psychiatrist performing the donor evaluation in standard postdonation follow-up and that 93% of LLDs are offered the care of the mental health specialist 33 . Most programs did not provide psychosocial follow-up for declined donors perhaps in the context of Mathur’s findings that nondonors’ quality of life was better than the living donors’ 34 .…”
Section: Discussionmentioning
confidence: 99%